2017
DOI: 10.11606/s1518-8787.2017051007033
|View full text |Cite
|
Sign up to set email alerts
|

Structure and work process in primary care and hospitalizations for sensitive conditions

Abstract: OBJECTIVE The objective of this study is to investigate whether the characteristics of the structure of primary health units and the work process of primary care teams are associated with the number of hospitalizations for primary care sensitive conditions.METHODS In this ecological study, we have analyzed data of Brazilian municipalities related to sociodemographic characteristics, coverage of care programs, structure of primary health units, and work process of primary care teams. We have obtained the data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
0
8
0
11
Order By: Relevance
“…For example, home visits, support from other professionals and referral to specialised care when needed have been associated with lower rates of avoidable hospitalisations. 42 In the state of Paraná, workers engaged in PMAQ have reported improvements in health information registries (allowing better monitoring of target populations) and the indicators from the external evaluation provided a good overview of what should be improved at team level. 43 On the other hand, qualitative studies conducted in state of Goiás and São Paulo showed a low perception of the PMAQ impact on clinical practices and work process, 15 44 mainly due to a top-down approach adopted during the implementation of PMAQ, lack of knowledge about the programme and absence of feedback regarding the results of external evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, home visits, support from other professionals and referral to specialised care when needed have been associated with lower rates of avoidable hospitalisations. 42 In the state of Paraná, workers engaged in PMAQ have reported improvements in health information registries (allowing better monitoring of target populations) and the indicators from the external evaluation provided a good overview of what should be improved at team level. 43 On the other hand, qualitative studies conducted in state of Goiás and São Paulo showed a low perception of the PMAQ impact on clinical practices and work process, 15 44 mainly due to a top-down approach adopted during the implementation of PMAQ, lack of knowledge about the programme and absence of feedback regarding the results of external evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…14 A estrutura e o processo de trabalho na APS são objeto de diferentes estudos, enquanto fatores fundamentais para a qualidade da atenção e integralidade do cuidado, 15,16 por conseguinte associados à redução de taxas de internação por condições sensíveis à atenção primária (ICSAP). 17 No caso das ações de alimentação e nutrição, a baixa adequação de estrutura e processo de trabalho pode influenciar, negativamente, aspectos da vigilância alimentar e nutricional, com ênfase na precarização do acompanhamento do desenvolvimento infantil e investigação dos casos de desnutrição. 18,19 Entre os itens analisados para a estrutura, insumos como sulfato ferroso, ácido fólico e sais para reidratação oral não estavam disponíveis em aproximadamente 10% das UBS.…”
Section: Discussionunclassified
“…Neste estudo, também foi observado um decréscimo de 71,88 %, o que reflete taxas consideravelmente menores, quando comparadas à média de internações do país (17). Tal fato pode ser explicado pelo aumento da cobertura da ESF em Teresina-PI, ao longo do período analisado, pois se sabe que ela contribui para a prevenção e tratamento de doenças que comumente geram internações (1,4,21). Em estudo realizado na Bahia, foi demonstrado o declínio das hospitalizações com a ampliação da cobertura da ESF, além de fazer menção a mudanças nos fatores demográficos e socioeconômicos que aconteceram em paralelo à queda das hospitalizações por CSAP e, provavelmente, exerceram influência positiva (5).…”
Section: Discussionunclassified